INVESTIGATING INSTAGRAM IN ENGLISH LANGUAGE LEARNING: EXPERIENCES OF INDONESIAN UNIVERSITY STUDENTS - Muluk, Safrul; Muzakki, Muhammad Fajar; Hanani, Fatayatul (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
Integrating ICT into English language learning is not a new phenomenon. It is considered as one of the instructional technology media in the teaching-learning process. Studies have shown that social media can be used to learn English. This study examined how students perceive the benefits and the challenges they face using Instagram for English language study. The researchers used the qualitative method of a single case study to examine and understand the phenomena, carried out at the English Education Department, Ar-Raniry State Islamic University, in Banda Aceh, Indonesia. A purposive sampling method was employed to select the respondents. The respondents must complete the Computer-Assisted Language Learning (CALL) course, and have an active social media with a minimum of 500 followers. As such, five students were selected to be involved in this research. The results of the research demonstrated that Instagram was perceived as beneficial by all respondents as it enabled them to browse and research materials helping them in the process of learning English skills. It also provides them with entertainment and revenue opportunities if used professionally. The findings also revealed that besides the benefits gained, using social media also posed negative effects such as inappropriate content, fraudulence, and perplexity that may arise from rich content.